Border and Identity Negotiations: An Analysis of 19th Century Migrations in the U.S (KULT_online, 2019)
Through archival research in libraries in the U.S and Mexico, Lim reveals the hidden history of racial categories and journeys that have been largely erased from both countries’ national consciousness by tracing the racial openness of the border from the 1880s to racial differentiation by the 1930s. Through laws, policies, and enactments, both states enforced national and racial uniformity, in turn, limiting migrants’ ability to cross these boundaries. Yet the immigrants employed the state’s political instruments, survival techniques, taking up different identities, maneuvering their claims to citizenship and belonging as different situations arise. Lim’s historical account stimulates a reflection on the challenging history of multiracial migration and the influence of opportunity structures in limiting or expanding immigrants’ mobility.